Global containment policy duration and long-term epidemic progression: A target trial emulation using COVID-19 data from 2020 to 2022 - Zhiyao Li; Zhen Wang; Xin Wang; Senke Chen; Wenxue Xiong; Chaonan Fan; Wenjuan Wang; Meng Zheng; Kunpeng Wu; Qun He; Wen Chen; Li Ling (International Journal of Infectious Diseases)
Objectives: Global countries often apply containment policies (CPs) to combat infectious disease surges. Whether countries with longer cumulative duration of CPs are associated with slower long-term epidemic progression necessitates a thorough evaluation. Methods: We collected CP and COVID-19 data of 185 territories during 2020-2022, with a total of 23 CPs. Using the target trial emulation and cloning-censoring-weighting approaches, we assessed the effectiveness of CPs with different cumulative durations in delaying countries from reaching the 1% and 10% cumulative infection incidence end points (i.e. 10,000 and 100,000 COVID-19 cases per million population, respectively) over a 3-year observation period. Results: For reaching the 1% cumulative infection incidence, recommending closing workplaces and limiting gatherings to 10 people, each presented that a longer cumulative duration of those CPs is associated with a lower proportion of countries achieving this end point throughout 2020-2022. For reaching the 10% cumulative infection incidence, mandatory bans on public events and domestic movements, closing public transports, and screening and quarantining inbound tourists, each showed similar associations. Notably, long-lasting border bans upon high-risk regions are associated with a higher proportion of countries reaching the 10% cumulative infection incidence. Conclusions: From the long-term perspective, we highlight CPs that warrant extending the duration to achieve slower epidemic progression. By contrast, our findings demonstrate the limited effectiveness of the ban on regions in slowing the long-term epidemic progression.